A new species of Heterangaeus Alexander, 1925 crane flies (Diptera: Pediciidae) from north-central Mongolia with first description of the larva for the genus - Podenas, Sigitas; Podeniene, Virginija; Gelhaus, Jon (Zootaxa, 2014)
A new species of Pediciidae, Heterangaeus mongolicus is described from specimens collected during the fieldwork of the Mongolian Aquatic Insect Survey Project in north-central Mongolia, Tov Aimag (district). Descriptions and illustrations of the distinguishing morphological features are provided. Habitat information is presented. Female ovipositor and larvae of Heterangaeus are described and illustrated for the first time. This discovery of Heterangaeus in Mongolia represents a 1700 kilometer extension of the known distribution for the genus.